Caracterización de la morbilidad materna extrema y la mortalidad materna en el hospital regional docente de Trujillo 2002-2006 - Cabrera Paz, Jorge Antonio (2009)
Objective: To determine the prevalence of extreme maternal morbidity (EMM), establish characterization events, and comparatively analyze EMM and maternal deaths; among pregnant women managed over a 5-year period in Educational Regional Hospital, hospital tertiary in Trujillo – Perú. Methods: Retrospective study based review of clinics histories of EMM and maternal death which occurred since 01 January 2002 and 31 December 2006. The EMM were compared with maternal deaths with respect to demographic features and disease profiles. Results: There were 16568 deliveries, 1853 maternal morbidities, 70 EMM and 35 maternal deaths. It was verified that the maternal morbidity, the MME and MM keep an order from diminution of frequency. Preeclampsia severe and the hemorrhage predominated with 62% maternal morbidity, whereas for MME the multisyatemic disease was the one that with 44% predominated. MM was brought by preeclampsia severe, multisystemic dysfunction, hemorrhages and septic shock, in sequence decreasing. Conclusion: The MM index was for multisystemic dysfunction, S. HELLP and renal dysfunction with 26%, 18% and 11%, respectively. The majority of the cases of MM (69%) happened outside the UCI. The reason of MM was of 211 per 100.000 live births. Relation MME/MM was 53, and the MME reason was 11 per 1000 live births.